Application of Regenerative Treatment for Tympanic Membrane Perforation With Cholesteatoma, Tumor, or Severe Calcification. Issue 4 (April 2018) - Kanemaru, Shin-ichi; Kanai, Rie; Yoshida, Misaki; Kitada, Yuji; Omae, Kaoru; Hirano, Shigeru
Abstract : Objective: To apply regenerative treatment for tympanic membrane (TM) perforation to patients with severe calcification of the TM, cholesteatomas, or tumors localized to the tympanic cavity. Study Design: Controlled clinical pilot study. Setting: General hospitals. Patients: Forty-five patients (age: 8–85; M = 19, F = 26) were selected from patients with or without TM perforation for the regenerative treatment. Twenty-five patients had cholesteatomas, 3 had tumors, and 17 had severe TM calcification. Patients were classified into three groups based on TM perforation size: less than 1/3 of the TM as Grade I (n = 5), 1/3 to 2/3 as Grade II (n = 19), and over 2/3 as Grade III (n = 21). Twenty patients who underwent standard tympanoplasty type I were selected as historical controls. Materials and Methods: Materials for the TM repair included gelatin sponge with basic fibroblast growth factor and fibrin glue. After lesions were removed through the TM perforation, gelatin sponge immersed in basic fibroblast growth factor was placed over the perforation. Fibrin glue was then dripped onto the sponge. Treatment efficacy was evaluated 6 months posttreatment. Results: Complete closure of the TM perforation was achieved in 91% (n = 41/45) of the patients in this regenerative treatment. Improvement in average hearing levels and air-bone gap were much better with this treatment than in the historical control group. Conclusion: This new regenerative therapy is useful not only for patients with simple TM perforations but also for those with cholesteatomas, tumors, or severe calcification without requiring conventional surgical procedures. This regenerative therapy is an easy, safe, cost-effective, and minimally-invasive treatment.